MOLECULAR DETECTION OF HELICOBACTER PYLORI IN PUD GASTRIC BIOPSY SAMPLES WITH REFERENCE TO VIRULENT GENES - SUGANYA K; PREMKUMAR A; SEKAR B; SEKAR T; SEKAR T; SUNDRAN B (International Journal of Pharma and Bio Sciences, 2016)
Helicobacter pylori is a known agent associated with Peptic ulcer disease(PUD), however the isolation and identification of H.pylori using conventional methodologies are challenging, hence a study was conducted to isolate Helicobacter pylori from biopsy samples of patients with PUD (Peptic ulcer disease) on selective agar media after the preliminary (Campylobacter like organism) CLO testing and genotyping using genus specific 16SrRNA and characterization of virulent factors viz. cagA, vacA and flagella A and nap A which are the predominant among the isolated clinical strains of Helicobacter pylori.The rate of positive H. pylori in the collected biopsies after the CLO test was 83% after amplification with genus specific 16SrRNA of Helicobacter pylori. The rates of the virulence genes cagA, vacA were 79.4% (62/78) and 25.6% (20/78), respectively. Seven patients were found colonized with both genotypes (cagA + vacA) having a rate of (3%). cagA status in association with vacA genotype has been implicated as a high risk factor for H. pylori related gastric pathologies. flagellaA, and nap A were found to be prevalent in all the positive samples of H.pylori. Fresh biopsy samples which were subjected to culture media containing antibiotics could obtain only few H.pylori isolates. Therefore a genotypic identification of 16sRNA was found to be highly sensitive for the detection of H.pylori than a bed side CLO test which could be positive for other Co-harboring bacterial species.